2015
DOI: 10.1590/s1984-82502015000100012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypericum perforatum on turning behavior in an animal model of Parkinson's disease

Abstract: Parkinson's disease (PD) is an age-related neurodegenerative disorder characterized by the slow and progressive death of dopaminergic neurons in the (substantia nigra pars compact). Hypericum perforatum (H. perforatum) is a plant widely used as an antidepressant, that also presents antioxidant and anti-inflammatory properties. We evaluated the effects of H. perforatum on the turning behavior of rats submitted to a unilateral administration of 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle as an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Their neuroprotective activities are attributed to their antioxidant potential, anti-inflammatory actions, and alteration of signaling pathways ( Basli et al, 2012 ; Moosavi et al, 2016 ). While managing neurodegenerative, novel therapeutic strategies support the application on antioxidant polyphenols as monotherapy or antioxidant cocktail formulation ( Vecchia et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their neuroprotective activities are attributed to their antioxidant potential, anti-inflammatory actions, and alteration of signaling pathways ( Basli et al, 2012 ; Moosavi et al, 2016 ). While managing neurodegenerative, novel therapeutic strategies support the application on antioxidant polyphenols as monotherapy or antioxidant cocktail formulation ( Vecchia et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these are effective in the treatment of neurological diseases; some are useful for cardiovascular, respiratory, and gastrointestinal diseases while others have chemotherapeutic and antibacterial effects. Some of the important phytochemicals of the plants (Table 4) including alkaloids (like nicotine and scopolamine) are reported to have anxiolytic, antidepressant, and anti-Parkinson activities [15][16][17][18], saponins (like bacosides) have been reported for anxiolytic, antiepileptic, antiamnesia, and neuroprotective and memory enhancement activities [19][20][21][22], terpenoids (like cannabigerol, tetrahydrocannabinol, and cannabidiol) are reported for their neuroprotective effects [23], flavonoids (like kaempferol, luteolin, quercetin, rutin, and hesperidin) have been reported for their anxiolytic, antidepressant, antiepileptic, anti-Alzheimer, and neuroprotective and memory enhancement activities [24][25][26][27][28][29][30], glycosides (like hastatoside and verbenalin) are reported for sleep promoting activity [31], steroids (like sitoindosides VII-X and withaferin-A) have been reported for anxiolytic activity [32].…”
Section: Resultsmentioning
confidence: 99%
“…In a study investigating the effects of H. perforatum in an animal model of PD, different doses of H. perforatum (100, 200, or 400 mg/kg) were administered to rats for 35 consecutive days and the turning behavior was evaluated at three different time points. The results showed that all doses of H. perforatum were effective in reducing the number of contralateral turns in all days of evaluation, which was proposed to be due to counteracting the overexpression of DA receptors in the lesioned striatum (Vecchia et al, ). Moreover, Gómez del Rio et al () evaluated the protective role of chronic administration of two standardized extracts of H. perforatum : SHP1 extract rich in hyperforin (6%) and SHP2 extract poor in hyperforin (0.2%) on rotenone‐induced PD in rats.…”
Section: Effects Of H Perforatum and Its Constituents On Neurodegenerative Diseasesmentioning
confidence: 96%
“…Parkinson's disease (PD) is a progressive neurodegenerative disorder with a variety of motor and nonmotor symptoms affecting more than 3% of individuals over the age of 75 (De Lau & Breteler, 2006). A limited number of studies have been conducted to investigate the effects of H. perforatum in animal models of PD (Gomez del Rio et al, 2013;Kiasalari et al, 2016;Vecchia et al, 2015). In a study conducted by Kiasalari et al (2016), treatment of intrastriatal 6-hydroxydopamine (6-OHDA)-lesioned rats with H. perforatum hydroalcoholic extract at a dose of 200 mg/kg/day attenuated the symptoms of PD and exerted protective effects via attenuation of DNA fragmentation, astrogliosis, inflammation, and oxidative stress.…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation